1980
DOI: 10.7326/0003-4819-92-1-45
|View full text |Cite
|
Sign up to set email alerts
|

The Rickettsia-like Organisms TATLOCK (1943) and HEBA (1959): Bacteria Phenotypically Similar to but Genetically Distinct from Legionella pneumophila and the WIGA Bacterium

Abstract: Two "rickettsia-like organisms," TATLOCK and HEBA, isolated from human blood via guinea pigs and embryonated eggs in 1943 and 1959, respectively, have been cultured on artificial media (charcoal yeast extract agar) for the first time and characterized. TATLOCK and HEBA have identical cultural, biochemical, and antigenic characteristics, as well as identical cellular fatty-acid composition and antimicrobial susceptibilities. These two bacteria have most of the cultural and biochemical characteristics of Legione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 24 publications
6
53
0
Order By: Relevance
“…From tissues, Tatlockia may be partly acid-fast (20). Although motility of some strains has been reported (10) and polar flagella have been demonstrated (10,12,20), these organisms are usually nonmotile after agar passage. Motility of some strains may be restored by passage on semisolid media.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From tissues, Tatlockia may be partly acid-fast (20). Although motility of some strains has been reported (10) and polar flagella have been demonstrated (10,12,20), these organisms are usually nonmotile after agar passage. Motility of some strains may be restored by passage on semisolid media.…”
Section: Resultsmentioning
confidence: 99%
“…Of these organisms, L. pneurnophila, WIGA (ALLOI), Pittsburgh pneumonia agent (PPA), HEBA, and TATLOCK possess common flagellar antigens (10, 12), a relationship which may exist among all flagellated members of this group of organisms and which may be of taxonomic importance. Cellular fatty acid analysis disclosed the presence of branched-chain fatty acids in unusually large amounts for gram-negative organisms (19), and characteristic fatty-acid patterns were described for L. pneumophila and for several others of these bacteria (7, 10,14,18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most important of these agents is Legionella micdadei. The bacterium that had been isolated in Pittsburgh (202) was initially called the "Pittsburgh pneumonia agent," but it was soon demonstrated that it was a new species of Legionella and that it had been isolated previously (124,202). In fact, the earliest recorded isolate of a Legionella species was a strain of L. micdadei that was recovered by Hugh Tatlock in 1943 during an outbreak of Fort Bragg fever.…”
Section: Philadelphia Epidemic Of Legionnaires Diseasementioning
confidence: 99%
“…The organism originally designated TATLOCK, after the individual who isolated the bacterium, has been subsequently classified as a strain of L. micdadei (14). It has been estimated that there are approximately 26,000 undiagnosied cases of legionellosis in the * United States each year (2).…”
Section: Discussionmentioning
confidence: 99%